Adoption of alkali-activated cement-based binders (geopolymers) from industrial by-products for sustainable construction of utility buildings-A field demonstration. (15th July 2022) - Revathi, T.; Vanitha, N.; Jeyalakshmi, R.; Sundararaj, Baskar; Jegan, M.; Rajkumar, P.R. Kannan
Abstract: There is an increasing interest towards using sustainable construction materials for reducing the consumption of natural resources and maximising the utilisation of industrial waste. Alkali activated alumina silicates sourced from industrial by products are environmentally friendly as they leave a low carbon footprint. In this research, performance-based mixes were designed in which a competitive cementitious binder (0% Ordinary Portland Cement) comprising a blend of fly ash–GGBSGround granulated blast furnace slag as a solid precursor and mixture of sodium hydroxide and sodium silicate was produced and utilised in the construction of a utility building after a comprehensive study. As a result of using the Alkali activated fly ash and slag (AAFS) binder, the formation of reaction product sodium-/calcium-containing alumino silicate hydrate gel of type N-A-S-H and C-A-S-Hnetworkyielded high compressive strength, good bond strength with steel and lower deterioration of the matrix on sulphuric acid exposure, which were confirmed from various test results. In-situ precast products of both structural and non-structural elements, viz. blocks, bricks, window/door frame and slabs of various sizes, were fabricated using local materials andproper training was provided to skill the workers to produce them. Different grades of concrete were produced (M20–M40) and utilised in different stages of the construction of the utility building rural children care centre. The field trials, testing methods, monitoring of various stages of the constructions and challenges are presented in this paper. The findings of this research would help in designing suitable user-defined geopolymer mixes in construction and if this technology becomes ubiquitous in the construction industry, it can contribute to reducing the adverse effects of climate change due to environmental degradation. Graphical abstract: Image 1 Highlights: Preparation of an ambient temperature cured geopolymer that serves a structural function. Field trials to fabricate various precast products with the desired properties. Demonstrated the building construction with local materials provided some conditions can be met on site. The combination R & D and access to industrial-scale application raise the awareness of this geopolymer technology.